Analisis Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak UMKM dalam Melaksanakan Kewajiban Perpajakan pada Masa New Normal UMKM di Kecamatan Pedurungan - Lili Wijayanti; Ceacilia Srimindarti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The country's economy is the same as the household economy which recognizes sources of income and expenditure items. One source of state revenue is tax which is a very important income for the implementation and improvement of national development. Realizing this, the government always promotes the importance of taxes for national development. This study aims to examine the effect of Taxpayer Awareness, Knowledge and Understanding of Tax Regulations, Tax Sanctions, and Fiscal Services on taxpayers. There are several factors that influence MSME taxpayer compliance. These factors include taxpayer awareness, knowledge and understanding of taxpayers, tax sanctions, and tax authorities services. Taxpayer awareness is one of the most important factors influencing the level of taxpayer compliance. The object of research is a research target that explains what and or who will be the object of research. The object in this study is the MSME taxpayer. The analytical tool used in this study is regression. The model test performed includes the F test, namely the overall (simultaneous) test and the coefficient of determination, while the t test is used for partial testing. Based on the test results show that the Taxpayer has no effect on Taxpayer Compliance. Knowledge and Understanding of Tax Regulations has a positive and significant effect on Taxpayer Compliance. Tax sanctions have a positive and significant effect on taxpayer compliance. Fiscal Services have no effect on Taxpayer Compliance.